2003
DOI: 10.1152/ajpendo.00112.2003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prolonged endurance cycling and recovery diet on intramuscular triglyceride content in trained males

Abstract: Intramuscular triglycerides (IMTG) are assumed to form an important substrate source during prolonged endurance exercise in trained males. This study investigated the effects of endurance exercise and recovery diet on IMTG content in vastus lateralis muscle. Nine male cyclists were provided with a standardized diet for 3 days, after which they performed a 3-h exercise trial at a 55% maximum workload. Before and immediately after exercise and after 24 and 48 h of recovery, magnetic resonance spectroscopy (MRS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
83
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 55 publications
13
83
0
Order By: Relevance
“…by guest, on May 12, 2018 www.jlr.org Downloaded from sus type II fi bers from vastus lateralis ( 21,22,24,25 ). Thus, the greater lipid content of ODS (but not ODR) compared with L muscle is generally consistent with the higher proportion of type I fi bers in ODS muscle.…”
Section: Potential Mechanisms Contributing To Greater Oxidative Fi Bementioning
confidence: 75%
See 1 more Smart Citation
“…by guest, on May 12, 2018 www.jlr.org Downloaded from sus type II fi bers from vastus lateralis ( 21,22,24,25 ). Thus, the greater lipid content of ODS (but not ODR) compared with L muscle is generally consistent with the higher proportion of type I fi bers in ODS muscle.…”
Section: Potential Mechanisms Contributing To Greater Oxidative Fi Bementioning
confidence: 75%
“…Greater levels of intramuscular lipid have been reported in obese compared with lean subjects (21)(22)(23), as well as in type I versus type II fi bers from vastus lateralis ( 21,22,24,25 ). It was therefore of interest to determine intramuscular lipid content in ODS, ODR, and L muscle ex vivo.…”
Section: Higher Intramuscular Neutral Lipid Content In Obesitymentioning
confidence: 99%
“…Boesch et al (2) revealed a decrease of IMCL in one subject performing a mountain bike ride over 3 h at about 70% of VO 2max , for the first time using 1 H-MRS to demonstrate that IMCL are metabolized during this form of exercise. In the following years, numerous reports on reduced IMCL levels during exercise were published and reviewed (17,20,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). It became obvious that both exercise duration and intensity are important factors in determining the reduction of IMCL (39).…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 99%
“…Since that time, however, and in spite of methodological problems of undertaking measurements of this substrate (Watt et al, 2002), there has been an increased interest in the utilization of intramuscular triacylglycerol (IMTG) stores during exercise and their replacement during recovery. There is now consensus that IMTGs provide a potentially important energy source for the contracting muscle (Watt et al, 2002), and emerging evidence that the consumption of a high carbohydrate/low fat diet in the recovery period after prolonged exercise may fail to provide for efficient recovery of this substrate (Decombaz et al, 2001;van Loon et al, 2003). Furthermore, one of the studies reviewed in the previous section identified that a moderate carbohydrate diet allowed a two-fold increase in IMTG stores compared with a high carbohydrate diet (Vogt et al, 2003).…”
Section: Fat As a Muscle Substratementioning
confidence: 99%